Single Particle Electron Microscopy Analysis of the Bovine Anion Exchanger 1 Reveals a Flexible Linker Connecting the Cytoplasmic and Membrane Domains - Jiang, Jiansen (Public Library of Science, 2013)
Anion exchanger 1 (AE1) is the major erythrocyte membrane protein that mediates chloride/bicarbonate exchange across the erythrocyte membrane facilitating CO(2) transport by the blood, and anchors the plasma membrane to the spectrin-based cytoskeleton. This multi-protein cytoskeletal complex plays an important role in erythrocyte elasticity and membrane stability. An in-frame AE1 deletion of nine amino acids in the cytoplasmic domain in a proximity to the membrane domain results in a marked increase in membrane rigidity and ovalocytic red cells in the disease Southeast Asian Ovalocytosis (SAO). We hypothesized that AE1 has a flexible region connecting the cytoplasmic and membrane domains, which is partially deleted in SAO, thus causing the loss of erythrocyte elasticity. To explore this hypothesis, we developed a new non-denaturing method of AE1 purification from bovine erythrocyte membranes. A three-dimensional (3D) structure of bovine AE1 at 2.4 nm resolution was obtained by negative staining electron microscopy, orthogonal tilt reconstruction and single particle analysis. The cytoplasmic and membrane domains are connected by two parallel linkers. Image classification demonstrated substantial flexibility in the linker region. We propose a mechanism whereby flexibility of the linker region plays a critical role in regulating red cell elasticity.